The impact of magnetic resonance imaging in the assessment of iron overload in heart and liver in transfusion-dependent thalassemic children: Minia experience - Ashraf M. El Sherif (SpringerOpen, 2021)
Abstract Background Thalassemia is the most prevalent single-gene disorder. Myocardial and hepatic iron depositions lead to complications and eventually death. We aimed to assess the diagnostic efficacy of magnetic resonance imaging T2* (MRI T2*) in quantifying iron overload in liver and heart in transfusion-dependent B-thalassemia major (TDT) children. Methods Prospective clinical study was carried on sixty children diagnosed with TDT. All of them underwent laboratory investigations, including CBC, serum iron, and ferritin levels. MRI T2* of the heart and liver was carried out to measure the iron overload and estimate the left ventricular ejection fraction (LVEF). Results Thirty-eight males and 22 females with TDT with a mean age of 13.23 years were included. Twenty cases (33.3%) had severe liver iron overload, while 36 (60%) had normal cardiac iron. There was a moderate significant negative association between hepatic and cardiac iron deposition (P = 0.03). All cases with severe cardiac iron overload had impaired LVEF below 56%. A non-significant positive association was noticed between cardiac iron deposition and LVEF in T2* (P = 0.08). A moderate negative significant association was detected between hepatic iron deposition and serum ferritin, while a fair negative significant association was found between serum ferritin and cardiac iron deposition with P values of 0.04 and 0.02, respectively. Conclusion MRI T2* is the gold standard for monitoring and follow-up of iron overload in the heart and liver. It should be routinely performed in all TDT children as liver iron, and serum ferritin do not reflect cardiac iron overload.